Alocação de recursos para aquisição de material bibliográfico em bibliotecas centrais universitárias - Ivone Guerreiro (1981)
A course of study with regard to the distribution of funds to purchase bibliographic material by central unioversity libraries. This studs has been realized through questionnaires sent to 61 institutions, 40 of them answered, so, according to the results obtained, the conclusion is as followas: a) In Brazil the distribution of funds for bibliographic material is not yet considered as being of mind the large number of theae libraries which leave this assignment to other mediums or departments of the university. b) A great part of the libraries under view, have no participation at all referring to the development of the collection, with exception as to the buracratic processo f buying the bibliographic material, c) The central administration of the libraries which leave the assignment the distribution of funds to other centers, may be questioned. d) Mosto f the libraries in question, never tried to create conditions to develop a distribution of funds less subjective, by means of using the information obtained through the basic services like the estimate of the collection, a study of the usuaries and na account of bibliographic material prices, in all áreas of human knowledge, because these services are not realized, and when they are, there is no consoderation as to their real finality. e)The number of auxiliary people dedicated to select and insignificante, that it takes the actual librarian to assume other tasksd, here with neglecting the development and growth of the collection. f) Wile foreign authors offer in litterature, sophisticated mathematical formulas as to distribution of funds, in brazil, most libraries, in this study, do not possess any standard or criterion as to distribution of funds. g) One cannot standarize the criterion referring to distribution of funds, because the libraries belong to istitutions with similar peculiar characteristics, and, being so, the criterion has to be appropriate and fit each proper situation.